Cumulative tea consumption is inversely associated with colorectal adenomas in adults: A cross-sectional study in a Taiwanese population. (August 2021) - Chen, Hung-Yu; Sun, Zih-Jie; Li, Chung-Hao; Chou, Yu-Tsung; Chang, Chih-Jen; Lu, Feng-Hwa; Yang, Yi-Ching; Wu, Jin-Shang
Highlights: This study showed tea consumption was inversely related to low-risk adenomas, regardless of the cumulative tea consumption amount. For high-risk colorectal adenomas, negative association was only found in the largest amount of tea consumption group (≥ 42 cup-years). Larger cumulative amount of tea consumption was negatively related to villous-rich adenomas and ≥3 adenomas, but not adenoma size ≥ 1 cm. Our study may provide a study direction for general population regarding the role of tea in preventing colorectal adenomas. Abstract: Purpose: This study examined the association between cumulative tea consumption over time and various colorectal adenomas as well as their pathology, number, and size. Methods: 7355 eligible subjects who underwent health check-ups with colonoscopies were recruited. They were classified into three groups: polyp-free, having low-risk colorectal adenomas, and having high-risk colorectal adenomas. The adenoma pathology, number, and size were collected. We defined 120 mL for each Chinese traditional teapot as a 'cup', and calculated the average daily cups of tea consumed. A 'cup-year' was defined as the daily cups multiplied by the years of tea consumption and was used to express the cumulative amount of tea consumption over time. Results: Compared to those with no habitual tea consumption, the lowest, middle, and highest tertiles of tea consumption were found to be inversely related to low-risk colorectal adenomas. For high-risk colorectal adenomas, a negative association was found only in the group with the highest tertile of tea consumption. An inverse association between the highest tertile of tea consumption and various features of high-risk colorectal adenomas was also found for villous-rich adenomas and the presence of three or more adenomas, but was not found to be related to adenoma size ≥1 cm. Conclusion: Tea drinking was inversely associated with both low-risk and high-risk colorectal adenomas. Only a larger cumulative dose of ≥42 cup-years was negatively associated with high-risk colorectal adenomas, especially adenomas with villous-rich pathology and when three or more adenomas were present.